2021
DOI: 10.5219/1533
|View full text |Cite
|
Sign up to set email alerts
|

A policy construction for sustainable rice food sovereignty in Indonesia

Abstract: As an agricultural country with large natural resources, Indonesia still has considerable problems in managing food security. This is evidenced by the lack of agricultural land and human resources that can support people's food needs so that the government still imports food from other countries. These issues as; it are feared that population growth and high food consumption power, social exclusion (marginalization of agricultural laborers and agricultural land) will cause food security vulnerability in the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This statement was supported by [11] who reported that based on their research through an in-depth interview study involving 169 respondents from stakeholders such as politicians, academicians, farmers,and students to determine policy construction for sustainable rice food sovereignty in Indonesia.…”
Section: Aspects Of Food Accessibilitymentioning
confidence: 96%
“…This statement was supported by [11] who reported that based on their research through an in-depth interview study involving 169 respondents from stakeholders such as politicians, academicians, farmers,and students to determine policy construction for sustainable rice food sovereignty in Indonesia.…”
Section: Aspects Of Food Accessibilitymentioning
confidence: 96%
“…Indonesia is also located in a tropical area with a climate suitable for extensive agricultural business so that Indonesia is an agricultural country [1]. The production of agricultural products for the provision of food, feed, industrial raw materials, and exports, as well as its role in the formation of GDP, employment, and sources of public income, make up the agricultural sector in Indonesia one of those that significantly contribute to the country's development [2].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to develop upland rice are faced with the problem of providing good quality seeds. Testing the quality and quality of seeds is very important because these tests can assure farmers that to avoid losses incurred during cultivation [4][5][6].…”
Section: Introductionmentioning
confidence: 99%